The Effect of Students’ Writing Ability through Brainstorming Methods towards English Learning Achievement in 2013 Curriculum - Ida Maulida ida maulida; Slamet Wahyudi Yulianto (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2021)
The process of writing has been seen as a problem for many students. This problem because students do not have the ability to develop ideas, creative solution. One of the methods to develop their ideas in writing by using Brainstorming Methods. Not only it, students have opportunities to develop their ideas using Jamboard in Education 4.0, especially it is suitable media in pandemic era. This research taught by brainstorming strategy using (Jamboard Application in Education 4.0), it is help students to develop innovative teaching strategies (brainstorming and concept mapping) on improving the students’ writing ability and creative thinking skill. Therefore, the purpose of this study is to the identify the methods applied by writing students’ ability through brainstorming methods towards English learning achievement in 2013 curriculum. The data were collected through observational used tests and questionnaires. The total samples used in this study were 38 students consisting of class XI IPS 1 of Public Senior High School in Subang. This research used an experimental method with the design of One Group Pretest Posttest Design. Moreover, considering, should provide more students to help them able to use the best techniques in teaching learning process online by using brainstorming methods (Jamboard in Education 4.0).